Global Security Conference Brisbane, Australia 28 Februari- 03 Mac 2010 - Rohasliney, Hashim (Pusat Pengajian Sains Perubatan, 2010)
APHIS- United States Department of Agriculture Rebecca Bech is the Deputy Administrator for Animal and Plant Health Inspection Service's (APHIS) Plant Protection and Quarantine (PPQ) program. Ms. Bech provides executW€ leadership and direction to a national~ dispersed staff responsible for safeguarding U.S. plant resources from destructive pests and diseases. She represents the USDA in international plant protection organiZations and serves as the U.S. representative for the International Plant Protection Convention. From April2007 to January 2008, Ms. Bech served as the Deputy Administrator for APHIS' Biotechnclogy and Regulatory Services program. She joined APHIS in 1986, serving in numerous pos~ion including, a plant pathology identifier, branch chief for the National Identification Services, and the Director for Scientific Services. She led the National lnvasW€ Species Initiative for the Department of Agriculture, serving as the USDA Uaison tor Invasive Species, representing the Secretary's office. Ms. Bech holds degrees in plant science and plant pathology and a Master's degree in education.